2021
DOI: 10.3390/ani11020464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mixed Invasions of Hypoderma bovis and Ostertagia ostertagi in Cattle on Milk Yield and Contents in Polish Dairy Farms

Abstract: Wide distribution of ecto- and endoparasites in cattle is a serious problem in the sustainability of a farm, due to the negative impact on animals’ health and productivity. The aim of this study was to determine the presence of antibodies against Ostertagia and Hypoderma in udder milk samples and the comparison of milk yield and content of the basic components of milk in ELISA-positive and ELISA-negative cows. Milk samples were collected from 148 lactating cows from 3 herds. Antibody detection was performed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Studies carried out in various countries show that the average extensiveness of gastrointestinal nematode infection (endoparasites) ranges from 61.96% in Mexico [ 115 ], 56% in Canada [ 116 ] to as much as 90% in Belgium and the Netherlands [ 117 ]. Wide distribution of ecto- and endoparasites in cattle is a serious problem in the sustainability of a farm, due to the negative impact on animals’ health and productivity [ 118 ]. Parasitic invasions are the major cause of production losses in dairy cattle herds including losses in milk production, decreased growth performance, impaired reproduction, and poor welfare [ 119 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies carried out in various countries show that the average extensiveness of gastrointestinal nematode infection (endoparasites) ranges from 61.96% in Mexico [ 115 ], 56% in Canada [ 116 ] to as much as 90% in Belgium and the Netherlands [ 117 ]. Wide distribution of ecto- and endoparasites in cattle is a serious problem in the sustainability of a farm, due to the negative impact on animals’ health and productivity [ 118 ]. Parasitic invasions are the major cause of production losses in dairy cattle herds including losses in milk production, decreased growth performance, impaired reproduction, and poor welfare [ 119 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…The severity of symptoms is determined by the parasite type, the level of infection, the food ration, the environment, and the animal’s overall health. In many cases, people are more vulnerable to bacterial and viral diseases [ 118 ]. Indigenous peoples of Punjab used different medicinal plants to treat endo- and ectoparasites infection such as, Achyranthes aspera, Allium sativum, Arundo donax, Bambusa bambos, Calotropis procera, Capsicum annuum, Cleome viscosa, Cocos nucifera, Convolvulus arvensis, Cucumis melo, Cyperus rotundus, Datura inoxia, Eruca vesicaria, Ficus religiosa, Lagenaria siceraria, Launaea procumbens, Mallotus pallidus, Mangifera indica, Medicago sativa, Melia azedarach, Nerium indicum, Ocimum basilicum, Piper nigrum, Psidium guajava, Punica granatum, Solanum Nigrum, Syzygium cumini, Tamarix aphylla, Tinosporia cordifolia, Trianthema portulacastrum, Vitis Vinifera, Withania coagulans, and Ziziphus jujuba (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rate of parasitism with H. bovis resulting from this study is fairly low compared with previously conducted studies, which reported prevalence rates between 32 and 43%, [16,17], 16.21% in Southern Romania [18]or with other countries: up to 85% in Italy [19,20], 67% in Turkey, 23% in Iraq [21], 43% in Belgium, 40% in France, 37.4% in Greece [22], 52.3% in Spain, 16% in Poland, 20% in Switzerland, up to 80% in China [23], and 31.1% in Albania [24]. The prevalence rate recorded 25 (2-7) 48 (6)(7)(8)(9)(10)(11)(12)(13)(14) 20 (1-5) 23 (5)(6)(7)(8)(9)(10) 106 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) May (Max-Min) June (Max-Min) p value equals 0.5861 By conventional criteria, this difference is considered to be not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have dealt with the comparative presentation and description of H. bovis , H. lineatum , H. diana , H. actaeon , and H. tarandi species, using both electron microscopy and molecular identification based on mitochondrial genes of cytochrome oxidase subunit I [ 8 , 9 ]. The stress caused by these clinical manifestations translates into decreased productivity due to the fact that animals cannot rest, eat or ruminate properly [ 2 ], especially if associated with internal parasitosis [ 10 ]. Grazing disturbance caused by flies during egg laying, especially in the case of H. bovis species, can lead to a behaviour known as gadding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation